PENERAPAN MANAGEMEN STRATEGIK ; SEBUAH LITERATUR REVIEW - Ika Agustina; Farhat Abas; Elvira Sitna Hajar; Aep Saefullah (POLITEKNIK LP3I JAKARTA, 2023)
This research aims to provide a comprehensive literature review on Strategic Management, focusing on its philosophy, stages, and models. The introduction presents the conceptual landscape of Strategic Management and the need for a profound understanding of the philosophies, stages, and models applied in a business context. The research method employs a literature review approach, specifically a Systematic Literature Review (SLR), analyzing 50 international and national research books and articles. Key findings involve the identification and analysis of the philosophies underpinning Strategic Management, critical stages in its implementation process, and effective models across various industries. The implications of this research encompass a enhanced understanding of the essence of Strategic Management for improved decision-making in dynamic business environments. Key words: Strategic Management, Philosophy, Stages, Models, Literature Review